Identification of yeast mutants with altered telomere structure. - Lustig, A J (1986)
The chromosomes of the yeast Saccharomyces cerevisiae terminate in a tract of simple-sequence DNA [poly(C1-3A)] that is several hundred base pairs long. We describe the identification of mutant yeast strains that have telomeric tracts that are shorter than normal. A genetic analysis of these strains indicates that these short telomeres are the result of single nuclear recessive mutations and that these mutations can be classified into two different complementation groups. The full expression of the mutant phenotype shows a very long lag (approximately equal to 150 cell divisions). From our analysis of these mutants as well as other data, we suggest that the duplication of the telomeric poly(C1-3A) tract involves two processes, semiconservative replication and untemplated terminal addition of nucleotides.